White matter apoptosis is increased by delayed hypothermia and rewarming in a neonatal piglet model of hypoxic ischemic encephalopathy - Wang, Bing (Neuroscience, 2015)
Therapeutic hypothermia is widely used to treat neonatal hypoxic ischemic (HI) brain injuries. However, potentially deleterious effects of delaying the induction of hypothermia and of rewarming on white matter injury remain unclear. We used a piglet model of HI to assess the effects of delayed hypothermia and rewarming on white matter apoptosis. Piglets underwent HI injury or sham surgery followed by normothermic or hypothermic recovery at 2 h. Hypothermic groups were divided into those with no rewarming, slow rewarming at 0.5°C/h, or rapid rewarming at 4°C/h. Apoptotic cells in the subcortical white matter of the motor gyrus, corpus callosum, lateral olfactory tract, and internal capsule at 29 h were identified morphologically and counted by hematoxylin & eosin staining. Cell death was verified by TUNEL assay. White matter neurons were also counted, and apoptotic cells were immunophenotyped with the oligodendrocyte marker 2′,3′-cyclic-nucleotide 3′-phosphodiesterase (CNPase). Hypothermia, slow rewarming, and rapid rewarming increased apoptosis in the subcortical white matter relative to normothermia (p<0.05). The number of white matter neurons was not lower in groups with more apoptosis after hypothermia or rapid rewarming, indicating that the apoptosis occurred among glial cells. Hypothermic piglets had more apoptosis in the lateral olfactory tract than those that were rewarmed (p<0.05). The promotion of apoptosis by hypothermia and rewarming in these regions was independent of HI. In the corpus callosum, HI piglets had more apoptosis than shams after normothermia, slow rewarming, and rapid rewarming (p<0.05). Many apoptotic cells were myelinating oligodendrocytes identified by CNPase positivity. Our results indicate that delaying the induction of hypothermia and rewarming are associated with white matter apoptosis in a piglet model of HI; in some regions these temperature effects are independent of HI. Vulnerable cells include myelinating oligodendrocytes. This study identifies a deleterious effect of therapeutic hypothermia in the developing brain.